Impact of total solar eclipse on spectral radiance characteristics of various objects and comparison of different vegetation indices - KASHYAPI, A.; SHAHA, S. K.; GULHANE, P. M. (MAUSAM, 2003)
The division of Agricultural Meteorology, Pune of I.M.D. conducted a study of anomalous radiation environment during the last total solar eclipse period at Principal Evapotranspiration Observatory (PET) Canning, W.B. The spectral radiance characteristics from various objects viz. bare soil, G.T.R. calibration plate (coated uniformly with BaSO4), rice crop at late vegetative stage and rice crop at panicle (flowering) stage were measured from 23-25 October 1995 to in blue (0.45-0.52m), green (0.52-0.59m), red (0.62-0.68m) and in the portion of near infrared (0.77-0.86m) wavelengths, by use of multi-band ground truth radiometer (G.T.R.) and different vegetation indices were computed. The minimum values of spectral radiance were observed from all the four objects between 0830 to 0930 hrs IST on the eclipse day. The proportion of drop was the maximum in the portion of near infrared (NIR) band during the eclipse period for both the rice crops. The rice crop at late vegetative stage showed sharp drop in both RVI (ratio vegetation index) and NDVI (normalized difference vegetation index) values between 0830 to 0930 hrs IST, while the other rice crop at panicle (flowering) stage showed sharp fall (in both the values) at 0830 hr IST. Both the RVI and NDVI values for the bare soil showed fluctuations on the eclipse day between 0730 to 1000 hrs IST. The MGVI (modified green vegetation index) values indicated that on the eclipse day during the period of total eclipse, quantity of radiation reflected by different objects dropped in all the four bands.